The Productivity of The Roller Gin and Ways to Improve It (Texas Journal of Multidisciplinary Studies, 2021)
The article analyzes the process of increasing the efficiency of roller ginning of fine-staple raw cotton. A method for determining the productivity of existing roller gins is described, which shows that productivity depends on the activity of the gripping of the snare drum and the efficiency of pulling the fibers under the knife.